Stonehenge: The Little ‘Big Other’ - Parker Pearson, Mike (Journal of Urban Archaeology, 2023)
Abstract Whilst Stonehenge cannot be considered urban, this famous stone circle was part of a much larger complex which included not only other monuments and significant topographic features but also extensive areas of late Neolithic and Chalcolithic settlement during 2500-2200 bc. The unusually large settlement at Durrington Walls, less than 3 km to the east of Stonehenge, appears to have been occupied primarily seasonally and by people who brought their livestock from many different parts of Britain. With the arrival of Beaker-users, the settlement focus shifted to the west of Stonehenge. There is growing evidence that the Stonehenge complex was not a central place but a ‘peripheral place’, located on what may have been a long-term cultural boundary within southern Britain.